Comparing the Underwater Soundscapes of Four U.S. National Parks and Marine Sanctuaries - Haver, Samara M.; Fournet, Michelle E. H.; Dziak, Robert P.; Gabriele, Christine; Gedamke, Jason; Hatch, Leila T.; Haxel, Joseph; Heppell, Scott A.; McKenna, Megan F.; Mellinger, David K.; Van Parijs, Sofie M. (Frontiers in Marine Science, 2019)
Passive acoustic sensors provide a cost-effective tool for monitoring marine environments. Documenting acoustic conditions among habitats can provide insights into temporal changes in ecosystem composition and anthropogenic impacts. Agencies tasked with safeguarding marine protected areas, such as the U.S. National Park Service and U.S. National Oceanic and Atmospheric Administration’s Office of National Marine Sanctuaries, are increasingly interested in using long-term monitoring of underwater sounds as a means of tracking species diversity and ecosystem health. In this study, low-frequency passive acoustic recordings were collected fall 2014 - spring 2018, using standardized instrumentation, from four marine protected areas across geographically disparate regions of the U.S. Economic Exclusive Zone: Northwest Atlantic, Northeast Pacific, South Pacific, and Caribbean. Recordings were analyzed for differences in seasonal conditions and to identify acoustic metrics useful for resource assessment across all sites. In addition to comparing ambient sound levels, a species common to all four sites, the humpback whale (Megaptera novaeangliae), was used to compare biological sound detection. Ambient sound levels varied across the sites and were driven by differences in animal vocalization rates, anthropogenic activity, and weather. The highest sound levels (dBRMS (50 Hz-1.5 kHz) re 1 μPa) were recorded in the Northwest Atlantic in Stellwagen Bank National Marine Sanctuary (Stellwagen) during the boreal winter-spring resulting from bioacoustic activity, vessel traffic, and high wind speeds. The lowest sound levels (dBRMS (50 Hz-1.5 kHz) re 1 μPa) were recorded in the Northeast Pacific adjacent to a vessel-restricted area of Glacier Bay National Park and Preserve (Glacier Bay) during the boreal summer. Humpback whales were detected seasonally in the southern latitude sites, and throughout the deployment periods in the northern latitude sites. Temporal trends in band and spectrum sound levels in Glacier Bay and the National Park of American Samoa were primarily driven by biological sound sources, while trends in Stellwagen and the Buck Island Reef National Monument were primarily driven by anthropogenic sources. These results highlight the variability of ambient sound conditions in marine protected areas in U.S. waters, and the utility of long-term soundscape monitoring for condition assessment in support of resource management.